Cu/Co meta-interconnects for 112 Gbps high speed applications - Kim, Hae-in; Wilcher, Alexander; Bowrothu, Renuka; Yoon, Yong-Kyu (Frontiers in Electronics, 2025)
This paper presents an innovative interconnect approach called “meta-interconnect,” which utilizes a combination of copper (Cu) and cobalt (Co) metaconductor (Cu/Co-MC) to enhance signal integrity in the millimeter-wave (mm-wave) spectrum. The primary objective is to demonstrate reduced conductor losses from the skin effect compared to Cu at the 112 Gbps Nyquist frequency of 28 GHz. For the first time, a comprehensive parametric analysis is conducted using both simulation and experimentation methods to suppress the skin effect with Cu/Co-MC. Based on the optimization of Cu/Co-MC-based coplanar waveguide (CPW) transmission lines, a minimum insertion loss of only 0.08 dB/mm at 28 GHz, which is 0.06 dB/mm less than that of the Cu counterpart, has been demonstrated, which represents a 42.86% reduction in conductor power losses. Additionally, Cu/Co-MC-based CPWs meet the sub-0.1 dB/mm channel loss target. The study verifies the impact that the thickness and number of Cu/Co-MC layers have on device performances. This provides valuable insights into the optimizing MC configurations, which in this study are 250 nm thick Cu and 40 nm thick Co. Cu/Co-MC pairs with optimized layers and total thicknesses demonstrate significant improvements in insertion loss and thermal noise. These findings highlight the potential benefits of the Cu/Co-MC-based meta-interconnect technology for data center high-speed serial bus applications, offering a promising solution for achieving high signal integrity in the mm-wave spectrum, contributing to the overall understanding and its MCs translation to commercial applications.